1976
DOI: 10.1159/000251112
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acne vulgaris with the Retinoic Acid Derivative Ro 11-1430

Abstract: In a double-blind, randomized, group-comparative clinical trial, 31 patients with acne vulgaris received topical treatment for 6-8 weeks with a lotion containing either 0.05% retinoic acid or 0.1 % of the retinoic acid derivative Ro 11-1430. The side-effects erythema, desquamation and burning were significantly less frequent with Ro 11-1430 than with retinoic acid. The treatments appeared to be approximately equally effective in reducing the number of acne elements, but due to the limited number of patients st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…[3] did not find any significant difference as regards the clinical effect between retinoic acid and Ro 11-1430, but Ro 11-1430 had a better local tolerance. This controlled multicenter trial shows a more moderate effect of Ro 11-1430 compared with that of retinoic acid.…”
Section: Commentmentioning
confidence: 64%
See 1 more Smart Citation
“…[3] did not find any significant difference as regards the clinical effect between retinoic acid and Ro 11-1430, but Ro 11-1430 had a better local tolerance. This controlled multicenter trial shows a more moderate effect of Ro 11-1430 compared with that of retinoic acid.…”
Section: Commentmentioning
confidence: 64%
“…In a controlled clinical trial, C hris tiansen et al [3] demonstrated that this was the case also in patients with acne vulgaris. Owing to the limited number of patients, the trial was unable to determine whether or not the diminished frequency of side effects had been obtained without a concurrent loss of therapeutic effect.…”
Section: Retinoic Acidmentioning
confidence: 91%
“…The efficacy of therapy was evaluated at allocation and after 2, 4, and 6-8 weeks by a within-patient and a between-patient comparison based on a counting of the total number of acne elements on a limited area (19.6 cm2) as well as of the number of comedones, papules, and pustules, separately [1], The intensity of local reactions was ranked according to the four-point scale: none, slight, moderate, and severe.…”
Section: Methodsmentioning
confidence: 99%
“…Christiansen et al [ 1,2] found that the retinoic acid derivative Ro 11 -1430 (0.1% solution) caused less severe and less frequent local reactions, but had a lower therapeutic effect than retinoic acid (0.05% solution) in patients with acne vulgaris. The incidence and severity of side-effects were correlated with a higher non-compliance rate in the retinoic acid group [2].…”
mentioning
confidence: 99%
“…The ther apeutic effects of topically applied 0.1 % mo tretinide and 0.05% retinoic acid on acne vulgaris have been found to be similar [Christiansen et al, 1976[Christiansen et al, , 1977Braathen et al 1978], Benzoyl peroxide administered topically has been shown to have a good therapeutic effect on acne vulgaris [Liddel, 1974;Jo hansson and Sulionen, 1978], However, lo cal side-effects in the form of skin irritation were noted in 41% of the patients in the stu dy, and this effect seemed to be a toxic and not an allergic reaction.…”
Section: Introductionmentioning
confidence: 91%